Synthesis, structure, magnetic and magnetocaloric properties of a series of CrIII4LnIII complexes. (25th February 2016) - Blacque, Olivier; Amjad, Asma; Caneschi, Andrea; Sorace, Lorenzo; Car, Pierre-Emmanuel
Abstract : Magnetic properties and magnetocaloric effect of rare heterometallic Cr(iii )–Ln(iii ) complexes are reported. Abstract : The hydrothermal reaction of CrCl3 ·6H2 O and Ln(NO3 )3 · x H2 O in the presence of di(2-pyridil)ketone, and sodium acetate in water leads to the formation of a series of [Cr4 Ln(CH3 COO)(pyCOO)((py)2 COO)4 ]·(NO3 )2 · n H2 O complexes (with Ln = Gd(iii ), Tb(iii ), Dy(iii ), and n = 19 or 20). The four newly synthesized complexes were characterized by single crystal X-ray diffraction technique and their magnetic properties were fully investigated by dc (direct current) and ac (alternating current) magnetic susceptibility measurements. Single crystal X-ray studies revealed that the dysprosium derivative crystallizes as two different structural forms: a triclinic P 1̄ form and a monoclinic P 21 / n form. The gadolinium and the terbium derivatives were isostructural to the dysprosium monoclinic form. Surprisingly, full static and dynamic magnetic studies revealed that none of the synthesized complexes exhibit single molecule magnet behaviour, while the gadolinium derivative displays a magnetocaloric effect (MCE).